Valor de mercado na presença de swap cambial como instrumento de hedge: um estudo de empresas do setor siderúrgico - Gustavo Alves da Costa (2005)
For years we have seen a discussion between academics and students of finance about maximization of value to the shareholder. This discussion is controversial due to the fact that it is not easy to identify the variables that explain the return to the shareholder. One of thesevariables could be exemplified by the use of company derivatives. So it became important to discuss this relation between derivatives and companys value. With this goal, the work developed contributes to the improvement of finance studies in Brazil and the impact of theseinstruments in the market value of the companies. Thus, the present work consisted in identifying and analyzing the impacts in the binomial risk and return, generated by use or not of derivatives, specifically swap as currency hedge. In order to reach this goal, the propositions by Modigliani and Miller (1958) and the portfolio selection technics and thesetting up of Efficient Frontiers, proposed by Markowitz (1952) were mainly used, considering the biggest steel companies in Brazil. The results show that steel companies that used currency swap, from march 1999 to march 2004, presented a weaker performance when compared to those that did not use derivatives. Therefore, except for the limitations of the work, it could not be proved that the use of derivatives, specifically currency swap by the companies, maximize the shareholders equity. The use of derivatives in Brazil could result from other factors such as: taxation of financial instruments and impacts in the tax benefits,agency costs and indifference of investors in relation to the use of currency swap.